2015
DOI: 10.15713/ins.ijdhc.6
|View full text |Cite
|
Sign up to set email alerts
|

Areca Nut Chewing Habit in Preschoolers: Two Rare Case Reports and Literature Review

Abstract: Areca nut chewing habit is common in adult age group worldwide. However, reports of such cases in children are rare. This paper aims to present two cases of areca chewing in preschoolers and its oral manifestations. This case report describes two cases of areca nut chewing habit in 5 and 6 years old girls and its oral manifestations along with the literature review. Myth: "Areca Nut chewing can cure iron deficiency anemia." Educating the society about the myths prevalent in society about its usage is very impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
2
0
3
Order By: Relevance
“…A study reported 81.02% of school children consumed local brands of sweetened areca nut with the majority found among the government school children 17 . The habit was also reported at a very young age among 4-and 6-year-old pre-schoolers because of some advantageous myths related to the use of areca nut 18 . The increase in the burden of OSMF in India and across the nations is evident from the increase in the reported publications which rose 66.26% from the year 1967 to 2016 with India contributing highest toward the increase 19 .…”
Section: Dash Ks Et Al Herbal Alternatives In Early Stages Of Osmfmentioning
confidence: 99%
“…A study reported 81.02% of school children consumed local brands of sweetened areca nut with the majority found among the government school children 17 . The habit was also reported at a very young age among 4-and 6-year-old pre-schoolers because of some advantageous myths related to the use of areca nut 18 . The increase in the burden of OSMF in India and across the nations is evident from the increase in the reported publications which rose 66.26% from the year 1967 to 2016 with India contributing highest toward the increase 19 .…”
Section: Dash Ks Et Al Herbal Alternatives In Early Stages Of Osmfmentioning
confidence: 99%
“…Badan Internasional untuk Penelitian tentang Kanker telah mengklasifikasikan pinang sebagai karsinogen Grup 1 dan telah dikaitkan dengan kanker mulut dan orofaringeal, lesi oral, leukoplakia oral,fibrosis submukosa, penyakit gusi, dan kanker faring serta esofagus (Jeng et al, 2014). Penelitian terbaru telah mengungkapkanbahwa pengunyah sirih memiliki tingkat ketergantungan yang sama dengan perokok (Papke, 2018). Selanjutnya, penelitian ini menunjukkan bahwa sebagian besar pengunyah sirih dan perokok memiliki sikap yang sama mengenai niat mereka untuk berhenti (Little et al, 2014).…”
Section: Aunclassified
“…Pada berbagai evaluasi sumber pengenalan kebiasaan mengkonsumsi sirih pinang maka untuk anak laki-laki adalah teman teman sebayanya sementara untuk anak perempuan sumber pengenalan mengkonsumsi sirih pinang adalah dari keluarganya (Prajapati et al, 2015). Sedangkan penelitian yang dilakukan di Kabupaten Kupang sumber pengenalan mengkonsumsi sirih pinang baik laki-laki maupun perempuan adalah orang tuanya belajar mengkonsumsi sirih pinang dari orang tuanya (Ngadilah & Pinat, 2019).…”
Section: Aunclassified
See 1 more Smart Citation
“…Based on research conducted in the UK on immigrants from South Asia, it is said that the habit of chewing betel for certain communities gives a sense of invigoration, confidence, eliminating boredom, helps relieve stress and is believed to strengthen teeth (Flora, Mascie-Taylor, & Rahman, 2012). On the other hand, some researchers declare a habit of chewing betel is harmful to oral health, the compounds produced from betel and sirih pinang give a bad effect on oral health, and become the cause of oral cancer.. (Farzeen, 2008); (Prajapati, Nayak, Nayak, & Shah, 2015), (Oakley, Demaine, & Warnakulasuriya, 2005), (Prajapati et al, 2015), (Trivedy, Craig, & Warnakulasuriya, 2002), (Sahitha, 2014), (Constance & Lusher, 2019), (Little, Pokhrel, Murphy, Kawamoto, & Suguitan, 2014), (Shah, 2012), (Williams, Malik, Chowdhury, & Chauhan, 2002).…”
Section:  Introductionmentioning
confidence: 99%